Analisis Implementasi dan Efektivitas Zakat Produktif dalam Meningkatkan Kesejahteraan Mustahik di BAZNAS Kabupaten Sintang, Kalimantan Barat - Teti Arnita; Ichsan Iqbal; Syahbudi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Productive zakat is a strategic instrument of Islamic economics in empowering beneficiaries (mustahik) and promoting sustainable welfare. BAZNAS of Sintang Regency, West Kalimantan, has implemented a productive zakat program through business capital assistance, training, and mentoring; however, its outcomes vary among beneficiaries. This study aims to analyze the implementation of the productive zakat program and the factors influencing its effectiveness in improving mustahik welfare. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and document analysis. Research informants include BAZNAS managers, mustahik, muzakki, community leaders, and local government representatives. Data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing, supported by descriptive quantitative data comparing mustahik income before and after receiving productive zakat. The findings indicate that the productive zakat program has been implemented systematically and contributes to increased income and economic self-reliance of most beneficiaries. Program effectiveness is influenced by amil managerial capacity, quality of business mentoring, utilization of information technology, local government support, and public zakat literacy